Romans at War Soldiers, Citizens, and Society in the Roman Republic - Armstrong, Jeremy; Fronda, Michael P. (Routledge Monographs in Classical Studies, 2020)
This volume addresses the fundamental importance of the army, warfare, and military service to the development of both the Roman Republic and wider Italic society in the second half of the first millennium BC. It brings together emerging and established scholars in the area of Roman military studies to engage with subjects such as the relationship between warfare and economic and demographic regimes; the interplay of war, aristocratic politics, and state formation; and the complex role the military played in the integration of Italy. The book demonstrates the centrality of war to Rome's internal and external relationships during the Republic, as well as to the Romans' sense of identity and history. It also illustrates the changing scholarly view of warfare as a social and cultural construct in antiquity, and how much work remains to be done in what is often thought of as a ""traditional"" area of research. Romans at War will be of interest to students and scholars of the Roman army and ancient warfare, and of Roman society more broadly.